Reliability, Availability, Maintainability, and Safety Analysis of Finger Joint Fu-King Furnimate Machine in Wood Manufacturing Industry - Tegar Tri Nugraha; Fransiskus Tatas Dwi Atmaji; Sheila Amalia Salma (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
The objective of this research was to investigate the performance of the Finger Joint Fu-King Furnimate machine, especially for the most critical component of this machine. Based on historical data of machine damage, the Finger Joint Fu-King Furnimate is the machine that has the highest-level frequency of damage. Reliability, Availability, Maintainability, and Safety (RAMS) methods are proposed to analyze the machine's historical data. The result shows that the reliability of machine performance at t = 160 hours is only 27.42%, but the availability of machines is quite high, which passed the standard of 95%. Meanwhile, the maintainability of the machine is relatively fast, which the repair time of its critical component is 8 hours. The low-reliability critical machine spare part affected the safety of the spare part which the Safety Integrity Level (SIL) in the lowest standard (level 1). In general, the novelty of this research is to combine the application of the RAM method as the basis for analyzing machine performance with a safety analysis of the selected critical machine subsystems.